艾滋病防治中的倫理和政策問題: Ethical and Policy Issues in AIDS/HIV Prevention and Treatment - QIU, Ren-Zong (International Journal of Chinese & Comparative Philosophy of Medicine, 1998)
LANGUAGE NOTE | Document text in Chinese; abstract also in English. 本文討論了艾滋病在中國大陸傳播引起的倫理和政策問題。作者首先指出在預防控制艾滋病問題上中國正處在十字路口。挨著作者分析了中國會不會成為艾滋病和艾滋病病毒感染的高發國，討論了制訂有效而合乎倫理的艾滋病防治政策的理論預設和價值以及評價政策的倫理學框架，討論了艾滋病治療和預防中的倫理和政策問題。 The AIDS/HIV prevention and control in China is at crossroad. At present, there are insufficient grounds for us to say that China will definitely become a country with a high HIV infection rate in the future. However, we have much less sufficient grounds for saying that China will never reach that stage. On the contrary, we have much more reason to say that it is very probable for China to become a country with high HIV infection rate if we leave the current policy unchanged. The reasons are: economic reforms associated with large scale population movements in unprecedented way; proliferation of all sorts of high risk behavior, presence of other STDs which facilitate the spread of HIV; the risk of iatrogenic spread through untested blood transfusion; the "sex revolution" with changes in patterns of sex behaviour and increased casual sex, multiple sex partners among the younger generation; most Chinese still do not know how to protect themselves; and the ethical and legal atmosphere necessary for effectively preventing the HIV epidemic has not been formed. The conventional public health approach is not sufficient to prevent or control an HIV epidemic. When the cases of HIV infection were detected one by one in China, health professionals and programmers believed that they could take a conventional public health approach to cope with HIV epidemic. But they are wrong. HIV infection is an epidemic so special that the conventional public health measures such as testing, reporting, contact tracing, isolation are inadequate or ineffective to control the epidemic. HIV is often spread among those groups who are usually marginalized or stigmatized by society through behaviours both confidential or private. An effective policy of preventing HIV cannot be insensitive to ethical issues. However, many of health professionals and programmers bypassed ethical issues emerged in the prevention of the HIV epidemic. Even some health educators, sexologists and officials believe that "AIDS is the punishment by God" or "AIDS is the punishment for promiscuity". For them suffering AIDS is not morally irrelevant, and thus the ancient conception of disease was revived. But this conception of disease has already proved wrong and harmful to the treatment and prevention of any disease, especially to HIV. The consequence entailed by this conception is that the IIIV positive and AIDS patients were discriminated against and stigmatized. When their positive serological status was disclosed, they were faced with the risk of being expelled from school or fired from working unit, even rejected for admission into hospital, and their tights to confidentiality and privacy were often infringed upon. If all these ethical issues cannot be properly treated, how can those persons in danger or risk get access to information, services, education, counselling and techniques necessary to prevent HIV infection? One Chinese adage says that "You cannot have fish and bear palm both". In the prevention of HIV epidemic we have to have the protection of public health and the safeguarding of individual rights. For controlling HIV epidemic what we need is not a repressive law, but a supportive law to build a supportive environment in treatment and prevention of AIDS/HIV. So the policy and law involving AIDS/ HIV should be reformed. DOWNLOAD HISTORY | This article has been downloaded 19 times in Digital Commons before migrating into this platform.